2005
DOI: 10.1007/s10708-005-4099-7
|View full text |Cite
|
Sign up to set email alerts
|

High density neighborhoods: Who enjoys them?

Abstract: To date, research into the subjective aspects of high density has focused mainly on the negative consequences of overcrowding. This study, in contrast, outlines some of the positive aspects of high density in neighborhoods, exploring the physical-spatial environment of two neighborhoods in the city of Haifa, Israel. It was found that while the relatively high residential density was similar in both neighborhoods (40 housing units per acre), this was more positively evaluated in one neighborhood as compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…The small body of research focusing on IUHD residents suggests that residential satisfaction may not necessarily be related to residential density per se, but to other neighbourhood factors, which may or may not be unique to dense locations, such as environmental quality, traffic and pollution, noise, lack of social cohesion and community involvement, lack of services and limited choice of residence (Bishop andSyme 1995, Howley et al 2009a). For example, Mitrany (2005) qualitatively explored the physical and social features which contribute to neighbourhood satisfaction in two high-density Jewish neighbourhoods in Israel and found that high density was rated more positively in the neighbourhood with greater transport services, facilities and open spaces within walking distance. Similarly, Kearney (2006) investigated residential satisfaction in various densities in a master-planned community in the USA and found density was not a predictor of residential satisfaction but the presence of shared outdoor areas was.…”
Section: Understanding Residential Satisfaction For Iuhd Residentsmentioning
confidence: 99%
“…The small body of research focusing on IUHD residents suggests that residential satisfaction may not necessarily be related to residential density per se, but to other neighbourhood factors, which may or may not be unique to dense locations, such as environmental quality, traffic and pollution, noise, lack of social cohesion and community involvement, lack of services and limited choice of residence (Bishop andSyme 1995, Howley et al 2009a). For example, Mitrany (2005) qualitatively explored the physical and social features which contribute to neighbourhood satisfaction in two high-density Jewish neighbourhoods in Israel and found that high density was rated more positively in the neighbourhood with greater transport services, facilities and open spaces within walking distance. Similarly, Kearney (2006) investigated residential satisfaction in various densities in a master-planned community in the USA and found density was not a predictor of residential satisfaction but the presence of shared outdoor areas was.…”
Section: Understanding Residential Satisfaction For Iuhd Residentsmentioning
confidence: 99%
“…Mitrany (2005) found a significant sociodemographicsÁland use relationship by identifying sociodemographic groups that favor compact land use. Others (Ewing 1995;Van de Coevering and Schwanen 2006) showed that if sociodemographics were controlled for, the land useÁtravel relationship became weaker.…”
mentioning
confidence: 99%
“…By definition, perceived land use is a subjective opinion held by the traveler (Churchman 1999; Mitrany 2005). For instance, although perceived density and crowding are both judged by the traveler, only crowding is evaluated in terms of the appropriateness of a given level (Churchman 1999).…”
mentioning
confidence: 99%